Anti-Bullying Assistance Based on Religious Moderation to Build Students’ Character - Nurdiana, Defi; Tasa, Evita Syela; Aufa, Arizqa Hidayatil; Iffa, Nur Zumratul (TAAWUN, 2025)
This service aims to assist students in preventing bullying through the application of religious moderation values to form a tolerant and moral character. The importance of this assistance is carried out because bullying can have a serious impact on the development of students’ character if it is not seriously considered. This service uses the Participatory Action Research method, which starts from the process of identification, planning, implementation, and evaluation or reflection involving students and teachers at MI Al-Muhsinun, Mojokerto City. The mentoring activities succeeded in increasing students’ understanding of the dangers of bullying and the importance of religious moderation values, such as tolerance, mutual respect, and cooperation across differences. Students show a change in attitude that is more open, empathetic, and able to resolve conflicts peacefully. This program has a positive impact on creating a safer, more inclusive, and harmonious school environment. In addition, this activity also strengthens the character of moral students, upholds the value of diversity, and supports efforts to prevent radicalism and violence in the educational environment. This program can be replicated in other schools as a model of character education based on religious moderation.